Unilateral carpal tunnel syndrome: an unusual presentation of nodular fasciitis. Issue 11 (30th November 2020) - Chouhan, Deepak; Ansari, Mohammed Tahir; Goyal, Devansh; Mridha, Asit Ranjan
Abstract : Nodular fasciitis is a benign, self-limiting proliferative disorder of fibroblast of uncertain aetiology, occurs frequently in the forearm. Nodular fasciitis in hand inducing carpal tunnel syndrome is exceptional. There are four cases of non-intraneural nodular fasciitis causing peripheral neuropathy that has been reported previously. We present the case of a 38-year-old man with features of unilateral carpal tunnel syndrome. Decompression of the median nerve performed subsequently along with excision of the lesion in a piecemeal fashion. Histopathological and immunohistochemical findings were consistent with nodular fasciitis. There were complete resolution of symptoms and no sign of recurrence at the end of 1 year after surgery.